Conformational preferences of α-fluoroketones may influence their reactivity - Pattison, Graham (Beilstein Journal of Organic Chemistry, 2017)
Fluorine has been shown in many cases to impart specific and predictable effects on molecular conformation. Here it is shown that these conformational effects may have an influence on reactivity through studying the relative reactivity of various α-halogenated ketones towards borohydride reduction. These results demonstrate that the α-fluoro ketones are in fact a little less reactive than the corresponding α-chloro and α-bromo derivatives. It is suggested, supported by computation, that this effect is due to reactive conformations in which the C–X bond is orthogonal to the carbonyl group for good orbital overlap being disfavoured in the case of fluoro ketones.
Keywords: α-halogenated ketones; conformational analysis; reactivity; stereoelectronic effects

(untitled) - Erian, A. W.; Sherif, S. M.; Gaber, H. M. (Molecules, 2003)

(untitled) - Dobson, L. S.; Pattison, G. (Chem. Commun., 2016)

(untitled) - Leng, D. J.; Black, C. M.; Pattison, G. (Org. Biomol. Chem., 2016)

(untitled) - Nash, T. J.; Pattison, G. (Eur. J. Org. Chem., 2015)

(untitled) - Thorpe, J. W.; Warkentin, J. (Can. J. Chem., 1973)

(untitled) - Bach, R. D.; Coddens, B. A.; Wolber, G. J. (J. Org. Chem., 1986)

(untitled) - O’Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Hunter, L. (Beilstein J. Org. Chem., 2010)

(untitled) - Zimmer, L. E.; Sparr, C.; Gilmour, R. (Angew. Chem., Int. Ed., 2011)

(untitled) - Fiorin, B. C.; Basso, E. A.; Tormena, C. F.; Rittner, R.; Abraham, R. J. (J. Phys. Chem. A, 2009)

(untitled) - Jones, R. N.; Spinner, E. (Can. J. Chem., 1958)

(untitled) - Krueger, P. J. (Can. J. Chem., 1973)

(untitled) - RamaRao, M.; Bothner-By, A. A. (Org. Magn. Reson., 1976)

(untitled) - Distefano, G.; Granozzi, G.; Bertoncello, R.; Olivato, P. R.; Guerrero, S. A. (J. Chem. Soc., Perkin Trans. 2, 1987)

(untitled) - Olivato, P. R.; Guerrero, S. A.; Santos, P. S. (Spectrosc. Lett., 1989)

(untitled) - Olivato, P. R.; Guerrero, S. A.; Hase, Y.; Rittner, R. (J. Chem. Soc., Perkin Trans. 2, 1990)

(untitled) - Wong, S. S.; Paddon-Row, M. N. (J. Chem. Soc., Chem. Commun., 1990)

(untitled) - Mohanta, P. K.; Davis, T. A.; Gooch, J. R.; Flowers, R. A., II (J. Am. Chem. Soc., 2005)

(untitled) - Saegebarth, E.; Krisher, L. C. (J. Chem. Phys., 1970)

(untitled) - Guerrero, S. A.; Barros, J. R. T.; Wladislaw, B.; Rittner, R.; Olivato, P. R. (J. Chem. Soc., Perkin Trans. 2, 1983)

(untitled) - Olivato, P. R.; Guerrero, S. A.; Modelli, A.; Granozzi, G.; Jones, D.; Distefano, G. (J. Chem. Soc., Perkin Trans. 2, 1984)

(untitled) - Abraham, R. J.; Jones, A. D.; Warne, M. A.; Rittner, R.; Tormena, C. F. (J. Chem. Soc., Perkin Trans. 2, 1996)

(untitled) - Pontes, R. M.; Fiorin, B. C.; Basso, E. A. (Chem. Phys. Lett., 2004)